Pablo de Rokha and José Angel Cuevas: From the nostalgia of the rural world to the subject of the marginal city (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article proposes to establish relationships between Pablo de Rokha (1994-1968) and José Angel Cuevas (1944) poetry, through the representation that both Chilean poets make about local, nacional, popular and urban identities. These features develop an imaginary, that goes from the mitification of the popular rurality and the degradation produces for the initial urban capitalism in Pablo de Rokha, until the marginalized subject of the dictatorial city with nostalgia about the old rural and urban world, also mitified in José Angel Cuevas.
Keywords: Pablo de Rokha; José Angel Cuevas; dentity; city; popular